Risk mapping in the customs field - Emilia Iordache (Romanian Economic Journal, 2008)
One of customs main tasks is to assess risks in the flow of goods. Risks are those factors that could influence Customs objectives. In pursuing those objectives it is important to have good knowledge of the risks that we face and the impact they might have on the objectives. The Customs administrations in the Member Stateshave opted to base the control on economic operators on the basis of risk management.The purpose of using risk management is to aim Customs’ control activities on risks rather then on random selected aspects or declarations.